Comelgetz prototype in learning prayers among children - Mohd Salihan Ab Rahman,; Nazlena Mohamad Ali,; Masnizah Mohd, (Penerbit Universiti Kebangsaan Malaysia, 2017)
In a natural user interface (NUI) interaction, users no longer need to use the input device to interact with a computer such as a keyboard or remote control. There are a number of issues mainly on misinterpretations of gestures that are often reported in NUI research. Among the user group is children. A study was conducted to explore the needs among children in understanding NUI interaction. This paper presents a NUI prototype in learning prayers among children. Event Driven Gesture Sequence Mechanism (EDGSM) was implemented in the prototype to address misinterpretations of gestures. This study aims to evaluate the ability of NUI prototype in learning and experience of children in learning prayers. The analysis found that the assessment of learning of NUI able to improve the learning performance and a better experience compared to traditional learning via video. However, the NUI prototype, which is not equipped with EDGSM mechanism, showed no significant increase in learning performance. The prototype equipped with EDGSM showed a significant result and managed to reduce misinterpretation of gestures by 43.27% compared to the prototype using standard mechanisms. This study indirectly encourages NUI designers and developers to focus on the problem of gestures misinterpretation and concern on the needs and capabilities of users, especially children.